Studies in Atatürk's Turkey : the American dimension - Criss, Bilge.; Harris, George S. 1931- (The Ottoman Empire and its Heritage, 2009)
Nearly all of the previous scholarship on Turkey and U.S. relations cover the Cold War period as well as current affairs with regard to security, strategy, and defense. Hence, the literature abounds with military orientation. This edited volume builds on a historical perspective and focuses on foreign relations, diplomacy, actors, mutual perceptions and reciprocity in diplomatic relations within the framework of the world conjuncture in the 1920s and 1930s. Relations with the U.S.A. have served as a balance in Turkey's Euro-Atlantic policy long before NATO was established. Likewise, re-building relations with the Republic of Turkey served U.S. interests in opening to the Near East and thus breaking away from its much lauded isolationist policy between the two world wars. Thus, the picture that emerges here is just as much a history of U.S. diplomacy as it is of Turkey.